2010
DOI: 10.1177/0310057x1003800206
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Fluid Prescription, Complications and Outcomes in Major Elective Open Gastrointestinal Surgery

Abstract: Perioperative fluid therapy and associated outcomes of patients undergoing major elective open gastrointestinal surgery are poorly understood. This study measured perioperative fluid therapy, complication rates and outcomes for major elective open gastrointestinal surgery in a tertiary care hospital. We obtained demographic data, operative details, fluid prescription, complications and outcomes in 100 patients. Patients were elderly and had multiple comorbidities. Median delivered intraoperative fluid volume w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
8
26
1
Order By: Relevance
“…The demographic and clinical features of our patients are consistent with other studies of similar types of surgery [1,10-13]. Likewise our complication rates appear to be similar to other university hospital hepatobiliary units [14,15].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The demographic and clinical features of our patients are consistent with other studies of similar types of surgery [1,10-13]. Likewise our complication rates appear to be similar to other university hospital hepatobiliary units [14,15].…”
Section: Discussionsupporting
confidence: 89%
“…Multivariate analysis was undertaken using a backward stepwise logistic regression model to identify factors associated with postoperative discharge by day 14, including all factors where the P value was less than 0.1 on univariate analysis. A cut off of 14 days represented the median length of stay for patients undergoing uncomplicated PD at our institution [1]. Odds ratios (OR) and 95% confidence intervals (CI) were reported where appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology has been endorsed by the National Health Service5 and is standard of care for all patients undergoing complex and prolonged hepatobiliary and pancreatic surgery in our institution. Previous research by our group has demonstrated that liberal fluid intervention in patients undergoing major pancreatic surgery is associated with a major complication rate of 50% 1. Inappropriate infusions of vasopressor agents in the setting of uncorrected hypovolaemia can lead to tissue hypoperfusion, organ dysfunction and ischaemia 6.…”
Section: Discussionmentioning
confidence: 98%
“…Even in experienced hands, perioperative morbidity rates are as high as 50% 1. We describe the perioperative management of a patient with pancreatic cancer and portal vein encasement.…”
Section: Introductionmentioning
confidence: 99%